(untitled) (Географический вестник=Geographical bulletin, 2017)
Впервые для Воткинского водохранилища сделана попытка оценить влияние добычи песчано-гравийной смеси на изменение береговой линии водоема. В основу такого подхода положены материалы отступления береговой линии и объемы добычи нерудных строительных материалов (по Хмелевскому и Сукмановскому месторождениям). INFLUENCE OF EXTRACTION OF SAND-GRAVEL MIXES ON CHANGE OF THE COASTAL LINE OF THE VOTKINSK WATER BASIN For the first time for the Votkinsk water basin attempt to estimate extraction influence sand-gravel mixes on change of a coastal line of a reservoir is made. Materials of deviation of a coastal line and volumes of extraction of nonmetallic building materials are put in a basis of such approach (on Hmelevsky and Sukmanovsky deposits).